2006
DOI: 10.1007/s00264-006-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodelling around HA-coated acetabular cups

Abstract: This study was designed to investigate bone remodelling around the cup in cementless THA. Previous studies indicate an advantage of better sealing of the bone-prosthesis interface by HA/TCP coating of implants, inhibiting polyethylene-induced osteolysis. One hundred patients gave informed consent to participate in a controlled randomized study between porous coated Trilogy versus Trilogy Calcicoat (HA/TCP coated). The cup was inserted in press-fit fixation. The femoral component was a cementless porous coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…It is therefore evident from the study that implantation causes localised increases in strains in a few locations around the acetabulum. These changes in load transfer mechanism after implantation are corroborated by published data [43][44][45][46]. In the clinical study by Wright et al [43], periacetabular bone-mineral density was assessed in a group of twenty-six patients who underwent primary total hip arthroplasty using press-fit acetabular cups.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is therefore evident from the study that implantation causes localised increases in strains in a few locations around the acetabulum. These changes in load transfer mechanism after implantation are corroborated by published data [43][44][45][46]. In the clinical study by Wright et al [43], periacetabular bone-mineral density was assessed in a group of twenty-six patients who underwent primary total hip arthroplasty using press-fit acetabular cups.…”
Section: Discussionsupporting
confidence: 54%
“…The compressive and tensile strains in rosettes 4 and 5 increased considerably after implantation, indicating high load transfer through the cortical shell on the rear surface of the acetabulum. However, a reduction in compressive strains for rosettes 1 and 2 was evident, which may not be entirely consistent with increased cortical load transfer observed clinically [43,44]. In the proximal ilium, a reduction in the tensile and compressive strains was observed in the rosette 3, indicating possible strain shielding.…”
Section: Discussionmentioning
confidence: 83%
“…A clinical bone remodelling study around cementless acetabular components by Meneghini et al [40] observed that relative bone density was increased in the periphery of the acetabulum, due to increased load transfer through that region. Laursen et al [39] reported bone mineral density changes that stabilised over the first postoperative year, which is consistent with an adaptive bone remodelling process. Similar results were reported by Manley et al [43], who observed using FE analysis that the implanted pelvis had less load transfer in the anterior and posterior regions of the acetabulum, and adjacent to the ischial facet as compared to the normal hip.…”
Section: Comparison Of Strains: Intact Versus Implanted Pelvisesmentioning
confidence: 65%
“…In clinical [12,23,24] and finite element [10,25] studies a 5% to 50% decrease was found in the ROI medial to the acetabular cup. The BMD preservation of RHA patients was most profound cranial to the cup (ROIs 1 and 5) for RHA patients.…”
Section: Discussionmentioning
confidence: 87%
“…Finite element analyses predict medial bone loss up to 50% caused by stress shielding, and a bone gain near the prosthetic rim of press-fit cups (which is the main loading site of the pelvis) [10]. Clinical DEXA studies on metal-on-poly (MoP) conventional THA confirm these results [11,12]. Little is known about periprosthetic acetabular BMD changes around MoM implants and resurfacing hip arthroplasty (RHA) in particular.…”
mentioning
confidence: 99%